Baking in America : - Patent, Greg (Houghton Mifflin Company, 2002)
This groundbreaking collection encompasses both sweet and savory favorites: yeast breads and quick breads, layer cakes and loaf cakes, doughnuts and fruit desserts, pies and simple pastries. Taking as his starting point 1796, the year the first American cookbook was published, Greg Patent, an accomplished baker, has mined sources from across the country for exemplary baking recipes by and for home cooks. Perusing old cookbooks, journals, and handwritten diaries from libraries and private archives, he has skillfully recreated treasured recipes or used them as inspiration for his own thoroughly up-to-date creations.